Synthesis and antimicrobial effects of cyclotriphosphazenes containing monocarbonyl curcumin analogs - Gul Seker, Mine; Akbal, Tugce; Atilla, Devrim; Avsar, Neslihan; Ibisoglu, Hanife (Marmara Univ, 2018)
Six novel bridged structure cyclotriphosphazenes (4a-f) were synthesized from the reactions of aryloxycyclotriphosphazenes [aryloxy= phenoxy (2a) and (2-naphthoxy) (2b)] with monocarbonyl curcumin derivatives [acetone (3a), cyclopentanone (3b) and cyclohexanone (3c)] for the first time. The structures of the compounds (4a-f) were defined by elemental analysis, FT-IR, mass and NMR (H-1 and P-31) spectroscopies. The antimicrobial properties of the compounds (2a, 2b, 3a-c and 4a-f) were screened in vitro against Escherichia coli ATCC 8739, Staphylococcus aureus ATCC 29213, Bacillus subtilis ATCC 6633, Bacillus cereus DSMZ 4312 and Candida albicans ATCC 10231. In addition, effective substance of 3b and 4c were evaluated Minimal Inhibition Concentration.
Keywords: Antimicrobial activity; mininimal inhibition concentration; phosphazene; curcumin